Comparative Analysis of Time Series Forecasting Methods for Predicting Spare Parts Demand in Supply Chains - Caliari, Ítalo P.; Figueiredo, Ravi B. D.; Silva, Diogenes W. F; Messias, Edierley B.; Haddad Neto, Mario (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2026)
Accurate demand forecasting prevents stockouts and excess inventory, but sparse data for many components hampers model building. To address this, interchangeable components were grouped, enabling analysis of aggregated warranty, repair, and Consumption Index (CI) data for 3,000 groups. Classical time series techniques, including the Simple Moving Average (SMA) and Exponential Moving Average (EMA) were evaluated along with different SARIMAX implementations. Performance analysis was conducted using the Root Mean Square Error (RMSE) and Sufficiency metrics. The results of this study highlight the effectiveness of simple approaches compared to more complex methods, such as neural networks and XGBoost, which did not outperform baseline algorithms in terms of RMSE and Sufficiency. However, simpler methods have limitations in capturing complex dynamics.